Chapter 47 The uses of citizenship in the post-Roman West - Martínez Jiménez, Javier (Taylor & Francis, 2023)
It has been a recurrent shortcoming in the historiography of late antiquity and the early Middle Ages to dismiss the importance of citizenship after Caracalla's edict, but especially after the fall of Rome. This tendency comes from the implicit assumption that citizenship in this period referred either to the vestiges of an outdated Roman citizenship or to a Christian spiritual model of civic belonging that focused first and foremost on a world to come. Building on recent attempts to reassess this orthodoxy, this chapter presents an overview of the ways in which citizenship and civic language continued to be useful and meaningful in the post-Roman Latin West. Covering the period from the fourth until the seventh century CE, it consists of four parts. Part 1 outlines the state of affairs in the late Roman empire, when Roman citizenship still functioned within the legal and political framework of a Roman state. Part 2 takes the story to the post-Roman West, discussing the continued use and development of Roman citizenship as a legal category after the disintegration of the West-Roman empire. Part 3 addresses the diverse and widespread role of local citizenships in the former Roman territories of the West. Part 4 deals with the appropriation and re-purposing of civic language in Christian discourse, the aims of which were by no means exclusively spiritual.